Multi‐directional anisotropy from diffusion orientation distribution functions. Issue 3 (7th February 2014) - Tan, Ek T.; Marinelli, Luca; Sperl, Jonathan I.; Menzel, Marion I.; Hardy, Christopher J.
<x xml:space="preserve">Abstract</x> Purpose To evaluate a model‐independent, multi‐directional anisotropy (MDA) metric that is analytically and experimentally equivalent to fractional anisotropy (FA) in single‐direction diffusivity, but potentially superior to FA in its sensitivity to the underlying anisotropy of multi‐directional diffusivity. Materials and Methods An expression for MDA was defined from the orientation distribution function (ODF) and its analytical relation to FA was derived. Simulations of single and crossed double‐fibers were performed using a compressed‐sensing‐accelerated diffusion‐spectrum‐imaging (CS‐DSI) scheme. In vivo brain imaging using CS‐DSI was performed on eight healthy subjects. MDA was compared with FA and with another ODF‐based metric known as generalized FA (GFA). Results In simulated single‐direction fibers, MDA was shown to be equivalent to FA (from FA = 0.2 to 0.8). In crossed fibers, MDA provided superior differentiation of the underlying anisotropy as compared to FA and GFA. In vivo analysis shows that the MDA was superior to both FA (P = 0.015) and GFA (P = 0.021) in terms of its relative accuracy in crossed fiber regions. Conclusion MDA provides a potentially superior measure of fiber anisotropy relative to conventional FA or GFA, and may be used to improve the assessment of disease in regions with multi‐directional brain fibers. J. Magn. Reson. Imaging 2015;41:841–850. © 2014 Wiley Periodicals, Inc.